Derivation of aortic distensibility and pulse wave velocity by image registration with a physics‐based regularisation term. (10th October 2013) - Barber, David C.; Valverde, Isra; Shi, Yubing; Brown, Alistair; Beerbaum, Philipp; Rodney Hose, D.
SUMMARY Analysis of the cardiovascular system represents a classical problem in which the solid and fluid phases interact intimately, and so is a rich field of application for state‐of‐the‐art fluid–solid interaction (FSI) analyses. In this paper, we focus on the human aorta. Solution of the full FSI problem requires knowledge of the material properties of the wall and information on vessel support. We show that variation of distensibility along the aorta can be obtained from four‐dimensional image data using image registration. If pressure data at one point in the vessel are available, these can be converted to absolute values. Alternatively, values of pulse wave velocity along the vessel can be obtained. The quality of the extracted data is improved by the incorporation into the registration of a regularisation term based on the one‐dimensional wave equation. The method has been validated using simulated data. For idealised vessels, the accuracy with which the distensibility and wave velocity can be extracted is high (1%–2%). The method is applied to six clinical datasets from patients with mild coarctation, for which it is shown that wave velocity along the aorta is relatively constant. Copyright © 2013 John Wiley & Sons, Ltd.